LEGAL REGULATIONS ON CHILD VIOLENCE ACCORDING TO THE PERSPECTIVES OF CRIMINOLOGY AND VICTIMOLOGY - timin, Tan; Alhakim, Abdurrakhman; Purba, Cindy Plenita (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
Violence against children is a serious problem that has a detrimental impact on the physical, mental and emotional development of children throughout the world. This research aims to conduct an in-depth analysis of legal regulations related to child violence from a criminological and victimological perspective. Through a normative and descriptive legal research approach, this research reveals that, although there have been efforts to regulate and protect children's rights, there are still weaknesses in the legal system that require further improvement. The results of this study highlight the need to improve the implementation of existing laws and the important role of understanding criminological factors and victim protection from a victimology perspective in handling child abuse cases. It is hoped that this research can provide guidance for improving policies, more effective implementation, and better protection for children who are victims of violence, creating a safer society and caring for children's welfare.Keywords: Child Violence, Criminology, Victimology